Mathematical Reasoning of Vocational High School Students on Mathematical Tasks in the Law of Demand Context - Ai Tusi Fatimah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2021)
This study aims to describe the mathematical reasoning abilities of vocational high school students in the business and management expertise in solving mathematical tasks in the law of demand context. This research uses the descriptive qualitative method. The participants consisted of six students categorized into three groups: high, medium, and low mathematical abilities. Participants from one of the vocational schools in Ciamis, Indonesia. Mathematical tasks to explore students' mathematical reasoning abilities in the law of demand context. The law of demand is a concept in business economics subjects. The task situation expanded as an alternative to solving more mathematical tasks—data from the results of student answers and interviews. Data analysis refers to the characteristics of mathematical reasoning, which consists of imitative and creative reasoning. The stages of data analysis are reduction, presentation, interpretation, inference, and verification. The results of data analysis show that all students tend to do imitative reasoning on each given task. Students tend to remember the law of demand formulas and perform mathematical procedures that they remember. Students often perform mathematical procedures that are not by the nature of mathematics so that the resulting solution is wrong. The law of demand questions designed to explore creative reasoning abilities has not been able to bring students to the flow of creative mathematical reasoning.